2016
DOI: 10.1016/j.jpain.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Resident Macrophages in Muscle Contribute to Development of Hyperalgesia in a Mouse Model of Noninflammatory Muscle Pain

Abstract: Macrophages play a role in innate immunity within the body, are located in muscle tissue, and can release inflammatory cytokines that sensitize local nociceptors. Here we investigate the role of resident macrophages in the non-inflammatory muscle pain model induced by 2 pH 4.0 injections 5 days apart in the gastrocnemius muscle. We demonstrate that injecting 2 pH 4.0 injections into the gastrocnemius muscle increased the number of local muscle macrophages, and depleting muscle macrophages with clodronate lipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 67 publications
4
45
0
Order By: Relevance
“…Involvement of ASIC3 in muscular mechanical hypersensitivity was initially established in a non‐inflammatory muscle pain model induced by acidic saline injections (Sluka et al, ). This model later found that ASIC3 in the resident macrophages were responsible (Gong, Abdelhamid, Carvalho, & Sluka, ). In the current DOMS model, the possibility of macrophage ASIC3 involvement was low if not zero, as accumulating mononuclear cells, including macrophages, were rarely observed in the entire cross sectional area of the LC muscle (Hayashi et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Involvement of ASIC3 in muscular mechanical hypersensitivity was initially established in a non‐inflammatory muscle pain model induced by acidic saline injections (Sluka et al, ). This model later found that ASIC3 in the resident macrophages were responsible (Gong, Abdelhamid, Carvalho, & Sluka, ). In the current DOMS model, the possibility of macrophage ASIC3 involvement was low if not zero, as accumulating mononuclear cells, including macrophages, were rarely observed in the entire cross sectional area of the LC muscle (Hayashi et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…The number of macrophages, particularly M1 macrophages, and IL‐1β mRNA expression both increased in immobilized muscle. Macrophages could contribute to the development of noninflammatory muscle pain in a mouse model and accumulate in skeletal muscle during cast immobilization . They are mainly classified into M1 and M2 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages also contribute to noninflammatory muscle pain development in mouse models . They accumulate in the immobilized skeletal muscles and release inflammatory cytokines, such as tumor necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β), and IL‐6 .…”
Section: Introductionmentioning
confidence: 99%
“…After muscle injury, macrophages regulate inflammation, tissue integrity and pain [22,6,23]. M1 (proinflammatory) and M2 (anti-inflammatory) macrophage subtypes contribute at different times during healing.…”
Section: Introductionmentioning
confidence: 99%